Oxidative electrochemical depolymerization of lignin using highly active self-standing electrocatalysts prepared by electrospinning of lignin - García-Rollán, Miguel; Toscano-de-los-Riscos, Manuel; Ruiz-Rosas, Ramiro Rafael; Rosas, J.M.; Rodríguez-Mirasol, José; Cordero-Alcántara, Tomás (Elsevier, 2025)
Electrooxidative depolymerization of lignin enables obtaining renewable value-added chemicals under soft operation conditions. However, current nickel foam electrodes do not fully utilize their active phase. In this study, non-woven mats consisting of metal-containing carbon nanofibers were prepared by electrospinning of lignin and Ni, Co and/or Pd solutions. These mats, without further processing and additives, were tested as self-standing electrodes in the electrooxidative depolymerization of alkaline kraft lignin solution using a filter press electrolyzer at room temperature. The fibrillar electrocatalyst containing 10 % wt of Ni (CFNi10) showed the most promising results, producing i) up to 77 % of oxygen-rich depolymerized lignin solid, ii) a water-soluble fraction yield up to 19.8 % wt iii) total vanillin yield of 1.1 % wt, using specific charges as low as 250 C/glignin, outperforming the commercial nickel foam electrode, and iv) full reusability. Consequently, the activity of the process is improved, while the amount of nickel deployed on the electrochemical cell is notably decreased from 30 down to 0.3 mg/cm2. The results of the present paper also demonstrate that lignin electrochemical depolymerization needs to be promoted by reactive oxygen species and/or in-situ generation of hydrogen peroxide.
Keywords: Lignina; Electrocatálisis; Polímeros - Degradación; Ingeniería química; Lignin; Electrocatalysts; Carbon nanofibers; Depolymerization; Electrooxidation; Aromatic monomers